Prevalence of rubella susceptibility among pregnant mothers in a community-based antenatal clinic in Malaysia: A cross-sectional study. - Cheong , Theng Cheong; Ee , Ming Khoo (SAGE Publications, 2008)
Introduction: Routine rubella antibody screening is not done for antenatal mothers in community health clinics in Malaysia. However, congenital rubella syndrome has persisted with its associated health burden.